Angiogenin and tRNA fragments in Parkinson’s disease and neurodegeneration - Prehn Jochen H M; Jirström Elisabeth (Acta Pharmacologica Sinica, 2020)
In this review, we summarise the evidence for a role of the ribonuclease angiogenin in the pathophysiology of neurodegenerative disorders, with a speciﬁc focus on Parkinson’s disease (PD). Angiogenin is a stress-induced, secreted ribonuclease with both nuclear and cytosolic activities. Loss-of-function mutations in the angiogenin gene (ANG) have been initially discovered in familial cases of amyotrophic lateral sclerosis (ALS), however, variants in ANG have subsequently been identiﬁed in PD and Alzheimer’s disease. Delivery of angiogenin protein reduces neurodegeneration and delays disease progression in in vitro and in vivo models of ALS and in vitro models of PD. In the nucleus, angiogenin promotes ribosomal RNA transcription. Under stress conditions, angiogenin also translocates to the cytosol where it cleaves non-coding RNA into RNA fragments, in particular transfer RNAs (tRNAs). Stress-induced tRNA fragments have been proposed to have multiple cellular functions, including inhibition of ribosome biogenesis, inhibition of protein translation and inhibition of apoptosis. We will discuss recent evidence of tRNA fragment accumulation in PD, as well as their potential neuroprotective activities.